Reading Study Model for Dyslexia Children Based on Mingle Technique - Irda Murni (Journal of ICSAR, 2017)
The education problem in Padang, based on research by Irdamurni (2013), 41.74% of dyslexia children have difficulty in learning, this problem has caused the increase of Elementary School children who have trouble in reading. Elementary School teachers do not have the competence to resolve the children problem, therefore it is necessary for a guide to assist the teachers in teaching children with dyslexia in reading. The purpose of this research is to develop a reading study model for children with dyslexia based on mingle technique. This research uses research and development (R & D) by Borg and Gall (2003). The subjects were dyslexia children who study in Padang high-class Elementary School. The research produces the reading study model to children with dyslexia that consists of (1) identification and assessment format, (2) learning programs plan, (3) guidebook for teachers, (4) guidebook for students, (5) the module on dyslexia and mingle technique